Legal regulation of supplementary cervid feeding facing chronic wasting disease. Issue 8 (19th August 2019) - Mysterud, Atle; Viljugrein, Hildegunn; Solberg, Erling J.; Rolandsen, Christer M.
ABSTRACT: The supplementary feeding of cervids is a widespread practice across the northern hemisphere. There are few studies, however, regarding the extent of feeding in space and time. There are adverse effects of supplementary feeding, of which the most severe are increased parasite and disease transmission. With the recent emergence of chronic wasting disease (CWD) among cervids in Norway, a legal regulation was issued that banned all supplementary cervid feeding. We quantified the spatial extent and intentions of feeding cervids across all of Norway using a questionnaire at the municipality scale. We also compared spatial extent of feeding before and after the feeding ban to shed light on the ability of regulations to control supplementary feeding. Supplementary feeding to increase winter survival and targeting roe deer ( Capreolus capreolus ) was more common (48.4% of the municipalities) than the feeding of red deer ( Cervus elaphus ; 20.5%) and moose ( Alces alces ; 7.4%). The main feeding period was January–March, but extensive feeding also occurred from November to December and in April. Reducing traffic accidents was also a motivation, particularly for the feeding of moose (14.5%), and this was the main motivation (86%) for public feeding. Among the 65.7% that responded, 53.3% reported they knew about supplemental feeding of cervids in their municipality. In the region with the first feeding ban, 80.2% of municipalities were feeding in 2015–2016 before the ban, which was reduced to 68.4% in 2016–2017 and remained at 68.4% in 2017–2018. In the remainder of Norway, 81.4% were feeding in 2015–2016, and 72.6% were feeding in 2016–2017, but after the ban, this increased to 78.6% in the harsh winter of 2017–2018. Our study highlights that regulations across broad scales may not be followed and that more spatially targeted regulations and increased enforcement are required for disease transmission to be more effectively combated. © 2019 The Authors. Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society. Abstract : A legal regulation was issued that banned all supplementary cervid feeding facing chronic wasting disease in Norway, but we found low levels of compliance to the regulation. Our study highlights that more spatially targeted regulations and increased enforcement are required for disease transmission to be more effectively combated.